Optimal capacitor placement in radial distribution networks - Gallego, R. A.; Monticelli, A. J.; Romero, R. (Institute of Electrical and Electronics Engineers (IEEE), 2001)
The capacitor placement (replacement) problem for radial distribution networks determines capacitor types, sizes, locations and control schemes. Optimal capacitor placement is a hard combinatorial problem that can be formulated as a mixed integer nonlinear program. Since this is a NP complete problem (Non Polynomial time) the solution approach uses a combinatorial search algorithm. The paper proposes a hybrid method drawn upon the Tabu Search approach, extended with features taken from other combinatorial approaches such as genetic algorithms and simulated annealing, and from practical heuristic approaches. The proposed method has been tested in a range of networks available in the literature with superior results regarding both quality and cost of solutions.
Keywords: capacitor compensated distribution lines; combinatorial mathematics; optimization methods